Intrauterine pregnancy with copper intrauterine contraceptive device in situ: A case report from Nepal. (October 2022) - Rana, Abilasha; Shrestha, Amit; Regmi, Anil; Aryal, Shreyashi; Karki, Pragya; Singh, Rewant
Abstract: Introduction: and importance: Intrauterine pregnancy on the background of intrauterine devices heralds its rare but possible failure. Despite having an excellent contraceptive pearl index, clients with copper-T may present with typical pregnancy symptoms. Case presentation: We present a case of a 22 year primigravida who after 42 months of successful use of copper-T, conceived an intrauterine pregnancy diagnosed at 7 weeks period of gestation. Clinical Findings and Investigations: A positive urine pregnancy test following cessation of menstruation for 2 months was reported by the patient on presentation. Urgent transabdominal ultrasound of the abdomen and pelvis revealed a gravid uterus containing a single gestational sac corresponding to 7 weeks of gestation. After a thorough explanation about possibility of viable pregnancy and also its pros and cons, she decided to terminate the pregnancy. Manual vacuum aspiration was done with removal of copper-T. Conclusion: Although ectopic pregnancy is a relatively common complication of intrauterine contraceptive device, it is necessary to consider the possibility of intrauterine pregnancy as a potential complication as well. Although, term pregnancies with excellent prognosis have been demonstrated in many studies after removal of intrauterine devices, close follow up is needed to identify misplaced copper-T and keep unwanted pregnancy at bay. Highlights: Intrauterine pregnancy in patients with intrauterine devices is rare but possible. Intrauterine pregnancy with a CU-T 380 A is rather uncommon. It is necessary to consider the possibility of intrauterine pregnancy as a potential complication of intrauterine device. MVA or office hysteroscopy technique avid possible management.